Do Workplace Smoking Bans Reduce Smoking? - Evans, William N; Farrelly, Matthew C; Montgomery, Edward (American Economic Review, 1999)
In recent years workplace smoking policies have become increasingly prevalent and restrictive. Using data from two large-scale national surveys, we investigate whether these policies reduce smoking. Our estimates suggest that workplace bans reduce smoking prevalence by 5 percentage points and daily consumption among smokers by 10 percent. Although workers with better health habits are more likely to work at firms with smoking bans, estimates from systems of equations indicate that these results are not subject to an omitted variables bias. The rapid increase in bans can explain all of the recent drop in smoking among workers relative to nonworkers.